(Almost) recursive identification of monetary policy shocks with economic parameter restrictions - Jan Pablo Burgard; Matthias Neuenkirch; Dennis Umlandt (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2023)
Recursively identified vector autoregressive (VAR) models often lead to a counterintuitive response of prices (and output) shortly after a monetary policy shock. To overcome this problem, we propose to estimate the VAR parameters under the restriction that economic theory is not violated, while the shocks are still recursively identified. We solve this optimization problem under non-linear constraints using an augmented Lagrange solution approach, which adjusts the VAR coefficients to meet the theoretical requirements. In a generalization, we allow for a (minimal) rotation of the Cholesky matrix in addition to the parameter restrictions. Based on a Monte Carlo study and an empirical application, we show that particularly the "almost recursively identified approach with parameter restrictions" leads to a solution that avoids an estimation bias, generates theory-consistent impulse responses, and is as close as possible to the recursive scheme.
Keywords: C32; E52; E58; 330; Monetary Policy Transmission; Non-Linear Optimization; Price Puzzle; Recursive Identification; Rotation; Sign Restrictions